Analysis of Farmers' Income and Welfare Deep Coconut (Cocos nucifera L) in Keritang District, Indragiri Hilir Regency - Khaswarina, Shorea; Yulida, Roza; Rapiqi, M.; Salamah, Umi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
The purpose of this research is to: (1) determine the income level of coconut farmers (Cocos nucifera L) (2) Analyze the level of welfare of coconut farmers (Cocos nucifera L) in Keritang District, Indragiri Hilir Regency. The data collection methods used in this study are primary and secondary data. Primary data was obtained by conducting direct interviews with coconut farmers in Keritang District, Indragiri Hilir Regency using a questionnaire, while secondary data was obtained from relevant agencies as well as previous research journals and literature studies. This study used a survey method with a total of 44 respondents of coconut farmers obtained using the Taro Yamane formula and sampling with simple random sampling method. The analytical tool used to answer the first objective is income analysis tool (μ = TR - TC). The analytical tool used to answer the second objective is the analysis of the level of welfare according to BPS 2022. The results of this study indicate that the average income of coconut farmers (Cocos nucifera L) in Keritang District, Indragiri Hilir Regency is IDR 56,084,645.45/farmer/ year or IDR 4,673,720.45/farmer/month and this study shows the welfare level of coconut farmers (Cocos nucifera L) in Keritang District, Indragiri Hilir Regency. The level of welfare of coconut farmers according to BPS indicators (2022) in Keritang District there are 30 farmers or 68.18% are at the level of welfare with the Good group and 14 farmers or 31.82% are in the category of sufficient welfare level.